Breach of emulsions from the process of extraction of oil palm by means of application of electromagnetic radiation (2008)
The process of extraction of oil palm seeks to separate principally the emulsions oil-waters down muds presents using technologies of sedimentation and/or centrifugation; nevertheless, the losses in different flows of the process persist, and to reduce them it implies increasing the size of the equipments. The work consisted of submitting two process flows: liquor of press and recovered of evaluated were from 10 s up to (even) 60 s with increases relations of dilution were evaluated oil/water and the results were compared with the profiles of speed and efficiency of sedimentation for samples of the same fluids without were radiated. Finally tests were realized to the oil to determine if they exist or not effects on the quality of the same one on the part ot the microwaves. In general, to submit the above mentioned emulsions to microwave during times than a minute, they improve the speed of sedimentation and specifically for recoverd ones of centrifugal also the efficiency of sedimentation is improved; demosntrating that it is possible to break the balances of charges and polarities in the emulsions to atmperature lower than the used one in the process (between 55°C-65°C). Thought the project does not allow the inmediate applicatio in the plants of benefit, if it demonstrates that a favorable effect of the microwaves exists in the breach of emulsions for what it is suitable to continue investigating in this field.